Cholinergic basal forebrain degeneration is associated with central fatigue in Parkinson’s disease - Li, Li; Zhang, Xiaodan; Wang, Mateng; Wu, Yuemin; Chen, Zhaoying; Jiang, Yafen; Rainer, Timonthy; Guan, Qiongfeng; Fan, Weinv (Frontiers in Neurology, 2025)
BackgroundCentral fatigue is a prevalent and debilitating non-motor symptom in Parkinson’s disease (PD), yet its neurobiological basis remains poorly understood. While cholinergic basal forebrain (CBFB) degeneration has been implicated in various PD symptoms, its specific relationship with central fatigue has not been systematically investigated using neuroimaging.MethodsIn this cross-sectional study, 49 patients with PD underwent 3.0 T brain structural magnetic resonance imaging (MRI) and completed the Fatigue Severity Scale (FSS). Gray matter density (GMD) and gray matter volume (GMV) of CBFB subregions [cholinergic nucleus 4 (Ch4) and cholinergic nucleus 123 (Ch123)] were quantified using voxel-based morphometry with validated probabilistic atlases. Multiple linear regression models examined associations between FSS scores and regional GMD/GMV, adjusting for age, sex, and total intracranial volume (TIV).ResultsFatigue severity showed significant negative correlations with bilateral Ch4 integrity across both morphometric measures. Specifically, higher FSS scores were associated with reduced GMD in total, left, and right Ch4, and with smaller GMV in total and right Ch4. A weaker but significant negative correlation was also observed between fatigue and left Ch123 GMD, whereas no association was found with Ch123 GMV. Crucially, parallel analyses of GMD and GMV yielded convergent results, reinforcing the robustness of the Ch4-fatigue relationship.ConclusionThis study provides initial neuroimaging evidence linking cholinergic basal forebrain structural integrity with central fatigue in Parkinson’s disease. The consistent associations observed between fatigue severity and bilateral Ch4 morphology, supported by parallel GMD and GMV analyses, suggest a potential role for CBFB degeneration in PD-related fatigue. While further validation is needed, these findings contribute to the growing evidence supporting cholinergic involvement in non-motor symptoms and highlight Ch4 as a promising region for future investigations into fatigue mechanisms.